Assess the effectiveness of pursed lip breathing exercise on selected vital parameters and respiratory status among patients with chronic obstructive pulmonary disease. - SOLOMON VIJAYAKUMAR, (International Journal of Pharma and Bio Sciences, 2017)
Chronic Obstructive Pulmonary Disease (COPD) is a devastating lung disease that progressively robs a person’s ability to breath. We are facing a dual challenge because not only COPD is rapidly increasing in prevalence, but also many people with COPD are unaware that they have the disease. With proper medication, aggressive rehabilitation, and the right attitude most patients regain some lost functions and enjoy a happier, more productive life. Objectives: To assess the vital parameters and respiratory status of patients with Chronic Obstructive Pulmonary Disease in experimental and control group before and after administration of pursed lip breathing exercise .Evaluate the effectiveness of pursed lip breathing exercise among the patients with Chronic Obstructive Pulmonary Disease in experimental group. Methodology: Quasi-Experimental design was used. A total of 60 COPD patients were selected by Non probability purposive sampling technique from medical wards of |Government Vellore Medical College and Hospital, Vellore. Descriptive and inferential statistics were used to analyse the data collected. The study result showed that there was definite improvement in mean score of vital parameters and respiratory parameters, ie., pulse -6.20, systolic BP -5.17, diastolic BP-4.33,respiratory rate -4.93, Sao2 -1.67 and PEFR-54.67 in the experimental group, P<0.001 by using pursed lip breathing exercise. Hence the study proved the purse lip breathing exercise to be a very simple yet effective measure in improving the vital parameters and respiratory status10 of COPD patients.